Two-pore domain K+ channel TASK-1 in human pulmonary artery smooth muscle cells and its regulation by the vasoconstrictor endothelin-1 - Tang, Bi; Justus Liebig University Giessen (My University, 2010)
The characteristics of the two pore-domain potassium channel and its modulation by endothelin-1 (ET-1) were tested by means of the whole-cell patch-clamp technique combined with TASK-1 small interfering RNA (siRNA) in primary human pulmonary arterial smooth muscle cells. We have found that the TASK-1 protein is present in primary hPASMC via immunofluorescence and immunoprecipitation methods. PCR studies detect only TASK-1 mRNA in primary and cultured hPASMC.Under whole cell voltage-clamp conditions, noninactivating K+ current is clearly but reversibly inhibited by anandamide, which is a direct and selective TASK-1 channel blocker. Its inhibition induces a significant membrane depolarization. As a consequence of the inhibition of the outward current, anandamide also influences the reversal potential of the current. The anandamide sensitive current is reversed close to -84 mV, the calculated Nernst equilibrium potential for K+ under these conditions. Moreover, under symmetrical K+ conditions in the same cell, anandamide causes a clear inhibition of the K+ current. The anandamide sensitive current is linear and reversed at or near 0 mV, the calculated Nernst equilibrium potential for K+ under these conditions. We have found that the TASK-1 channels are their extreme sensitive to variations in the extracellular pH. It behaves in a pH dependent manner in primary hPASMC across the full voltage range. A pH of 8.3 significantly hyperpolarizes the cells, whereas acidification causes a membrane depolarization in primary hPASMC (-10±1 mV versus 13±2 mV; n=5).By assessing the O2 sensitivity of this channel in primary hPASMC, under current-clamp conditions, we have found that hypoxia causes a marked cell depolarization (by 10±1 mV; n=9) and that the hypoxia-sensitive current reverses close to -84 mV.Further investigations, using the TASK-1 small interfering RNA (siRNA) technique show that TASK-1 knockdown causes a depolarization of the resting membrane potential compared to control cells (-26±1 mV versus -40±2 mV; P<0.05). Pretreatment of hPASMC with TASK-1 siRNA results in a lack of significant further suppression of the IKN by anandamide, acidosis, hypoxia, or ET-1.In order to detect the modulation by ET-1, we have found that ET-1 markedly reduces the TASK-1 current in primary hPASMCs and significantly and dose-dependently depolarizes hPASMCs. The concentration-response curve calculation shows that IC50 is 1.6 ± 0.3 nM (n = 5). The effect of ET-1 on the TASK-1 current is completely abolished by a pre-application of 10 uM anandamide or a pH of 6.3. The ET-1-sensitive current is reversed close to -84 mV, the calculated Nernst equilibrium potential for K+ under these conditions. Application of isoflurane (1mM) enhances the TASK-1 current, and this facilitation is blocked by ET-1.In order to investigate the possible physiological relevance of TASK-1 for the ET-1 induced pulmonary vasoconstriction, the ET-1-induced pressor response in the isolated perfused mouse lungs was carried out. ET-1 induces a dose-dependent increase in the PA pressure. The PA vasoconstriction is more pronounced when anandamide is given prior to ET-1. The application of 8 nM ET-1 increases PAP with 15.6 ± 2.3 mmHg. When anandamide is given prior to ET-1, the increase is 23.8 ± 1.0 mmHg (n =5).To investigate the possible involvement of the ET-1-mediated signal transduction in human PASMCs, we have employed different signaling molecular blockers and demonstrated that the endothelin-sensitivity of TASK-1 requires ETA receptors, phospholipase C (PLC), phosphatidylinositol 4,5-biphosphate (PIP2), diacylglycerol (DAG) and protein kinase C (PKC) in hPASMCs. However, caveolins are not involved in this process. Additionally, ET-1 stimulates the threonine phosphorylation of TASK-1, but not its tyrosine phosphorylation.Our results suggest that TASK-1 is expressed in human PASMC and is hypoxia-sensitive. Furthermore, TASK-1 is regulated by ET-1 involved in ETA-PLC-PIP2-DAG-PKC pathway at clinically relevant concentrations, which might represent a novel pathological mechanism related to pulmonary arterial hypertension.

In dieser Arbeit wurden die Effekte von Endothelin-1 (ET-1) am two-pore domain Kaliumkanal TASK-1 von humanen primären pulmonalarteriellen glatten Muskelzellen (PASMCs) geprüft. Für die Untersuchungen wurde die Patch-Clamp Methode mit der small interfering RNA Methode kombiniert.Mittels pharmakologischen Tools wurde der TASK-1 Kaliumkanal, der auch als Hintergrundkaliumkanal bezeichnet wird, in der Ganzzell-Konfiguration der Patch-Clamp Methode untersucht. Der nicht-inaktivierende Kaliumstrom des TASK-1 Kanals wurde durch Anandamide (spezifischer Blocker von TASK-1), durch extrazelluläre Azidose und durch Hypoxie inhibiert. Die Anwendung der small interfering RNA gegen TASK-1 führte zu einer Inhibierung des TASK-1 Stromes und zu einem Verlust der Effekte von Anandamide, Azidose und Hypoxie sowie zu einer signifikanten Depolarisation des Membranpotentials der humanen PASMCs (-26±1 mV vs. -40±2 mV; P<0.05). Die Existenz von TASK-1 wurde auch mittels PCR und Immunhistochemie bestätigt.Der sehr effektive Vasokonstriktor Endothelin-1 blockierte den TASK-1 Kanal in klinisch relevanten Konzentrationen signifikant. Der Effekt war dosisabhängig mit einer halb-maximalen Konzentration (IC50) von 1.6 ± 0.3 nM. Die Effekte von ET-1 am TASK-1 Kanal wurden durch Vorapplikation von Anadamide oder Azidose aufgehoben. Die Anwendung von ET-1 führte zu einer signifikanten Vasokonstriktion in den Pulmonalarterien in der isoliert-perfundierten Mauslunge.Weitere Untersuchungen zeigten, dass für die Effekte von ET-1 der Endothelinrezeptor A, die Aktivierung von Phospholipase C (PLC), Phosphatidylinositol 4,5-biphosphate (PIP2), Diacylglycerol (DAG) und Proteinkinase C (PKC) in humanen PASMCs essentiell sind.Diese Ergebnisse zeigen, dass TASK-1 für die Effekte von ET-1 eine zentrale Bedeutung hat und daher einen neuen Signalweg repräsentiert, der für die Entstehung der pulmonalen Hypertonie, aber auch für mögliche therapeutische Ansätze eine wichtige Rolle spielen könnte.
Effekte von Endothelin-1 (ET-1) am two-pore domain Kaliumkanal TASK-1 von humanen primären pulmonalarteriellen glatten Muskelzellen (PASMCs)
Keywords: pulmonary arterial vascular smooth muscle cells; TASK-1 potassium channel; ET-1; patch clamp; pulmonary hypertension; ddc:610